2018
DOI: 10.1089/ars.2017.7003
|View full text |Cite|
|
Sign up to set email alerts
|

A Dual AMPK/Nrf2 Activator Reduces Brain Inflammation After Stroke by Enhancing Microglia M2 Polarization

Abstract: We developed a novel class of hybrids (HP-1a-HP-1f) of telmisartan and 2-(1-hydroxypentyl)-benzoate (HPBA) as a ring-opening derivative of NBP. The most promising hybrid, HP-1c, exhibited more potent anti-inflammatory and neuroprotective effects in vitro and reduced brain infarct volume and improved neurological deficits in a rat model of transient focal cerebral ischemia when compared with telmisartan alone, NBP alone, or a combination of telmisartan and NBP. HP-1c had a therapeutic window of up to 24 h, amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 69 publications
10
117
0
Order By: Relevance
“…Interestingly, our results show that CX3CL1 also activated 5´-prime-AMP-activated protein kinase (AMPK), which has critical roles in regulating growth and reprogramming metabolism, as well as autophagy and cell polarity (Mihaylova & Shaw, 2011). Furthermore, it has been reported that microglial polarization to the M2 phenotype and reduction of oxidative stress are mediated through activation of AMPK and NRF2 pathways (Wang, Huang et al, 2018), what confirms our results. CX3CL1 also induced epidermal growth factor-receptor (EGF-R), which is involved in microglial migration (Qu, Liu et al, 2015).…”
Section: B Signalling Activationsupporting
confidence: 89%
“…Interestingly, our results show that CX3CL1 also activated 5´-prime-AMP-activated protein kinase (AMPK), which has critical roles in regulating growth and reprogramming metabolism, as well as autophagy and cell polarity (Mihaylova & Shaw, 2011). Furthermore, it has been reported that microglial polarization to the M2 phenotype and reduction of oxidative stress are mediated through activation of AMPK and NRF2 pathways (Wang, Huang et al, 2018), what confirms our results. CX3CL1 also induced epidermal growth factor-receptor (EGF-R), which is involved in microglial migration (Qu, Liu et al, 2015).…”
Section: B Signalling Activationsupporting
confidence: 89%
“…In addition to scavenging ROS directly, the activation of Nrf2 and the expression of its downstream genes may have protective effects against I/R damage, as validated by emerging evidence [18,19]. As one of the master regulators for defending against oxidative stress, Nrf2 binds to the antioxidant response element (ARE) in the nucleus and promotes a series of antioxidation gene expression [20]. The level of Nrf2 showed an inverted U shape after ischemic stroke, characterized by a robust increase from 2 h of OGD, a peak at 8 h, and then a decrease below baseline at~24 h in transient MCAO mice [21].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of metformin is not completely clear, but it involves inhibition of mitochondrial complex I, thus increasing the AMP/ATP ratio (El-Mir et al, 2000;Owen et al, 2000) and leading to activation of the energy sensor AMPK (Hardie, 2004;Rena et al, 2017). Importantly, AMPK activates NRF2 (Wang et al, 2017a;Zhao et al, 2017), and pharmacological targeting of this axis attenuates inflammation after stroke (Wang et al, 2017c) or endotoxin exposure Lv et al, 2017). Indeed, metformin activates NRF2 in an AMPK-dependent manner, resulting in inhibition of inflammatory responses in preclinical rodent models of transient global cerebral ischemia (Ashabi et al, 2015;Kaisar et al, 2017).…”
Section: E Repurposing Instead Of De Novo Drug Discovery and Developmentioning
confidence: 99%